The Wake Forest University School of Medicine Postbaccalaureate Research and Education Program (PREP): A Stepping Stone to Matriculation and Success in Biomedical Science Graduate Programs. - Diz, Debra I.; Gilliam-Davis, Shea; Gwathmey, TanYa M. (Journal of Best Practices in Health Professions Diversity: Education, Research & Policy)
Despite two decades of concerted efforts to increase the diversity of the biomedical sciences workforce, distinct populations remain poorly represented: Blacks, Latinos, Pacific Islanders, Native Americans, first-generation college students, and individuals with disabilities or from disadvantaged backgrounds. With grant support from the National Institute of General Medical Sciences (NIGMS), Wake Forest University School of Medicine (WFUSM) developed the Postbaccalaureate Research and Education Program (PREP) to facilitate their entry into biomedical sciences graduate programs. From 2001--2017, 80 students participated in a 1--2-year research-intensive internship simulating graduate school. As a result, 96% applied to PhD or MD/PhD programs; 92% entered PhD or other advanced degree programs, with 92% retention. These outcomes demonstrate the efficacy of a graduate-level preparatory program for diversifying the biomedical sciences workforce.